Non CF-bronchiectasis: Aetiologic approach, clinical, radiological, microbiological and functional profile in 277 patients. (July 2016) - Dimakou, Katerina; Triantafillidou, Christina; Toumbis, Michail; Tsikritsaki, Kyriaki; Malagari, Katerina; Bakakos, Petros
Abstract: Background and objectives: Non-Cystic Fibrosis (CF) bronchiectasis is common in Greece but little attention has been paid to the investigation of its aetiology, clinical, radiological, microbiological and lung function profile. Methods: We prospectively evaluated patients with non-CF bronchiectasis confirmed by high resolution computed tomography (HRCT) of the chest. Aetiology, clinical data, radiology score, microbiological profile and lung function were investigated. Results: We evaluated 277 patients (170 women) with bronchiectasis (mean age: 60.5 ± 16 years), 64% of them being non-smokers. Post-infectious (25.2%) and past tuberculosis (TB) (22.3%) were the most commonly identified underlying conditions, while no cause was found in 34% of the patients. The main symptoms were cough (82%), mucopurulent sputum (80%), dyspnea (60%) and haemoptysis (37%). Mean duration of symptoms was 9.7 (SD 10.7) years. Infectious exacerbations were observed in 67.5% of the patients with a mean frequency of 2.3 (SD 1.4) per year. The most frequent lung function pattern was the obstructive (43.1%) while 38% of the patients had normal spirometry. Pseudomonas aeruginosa was the most common pathogen yielded in sputum cultures (43%) followed by Haemophilus influenzae (12.6%). Patients with P. aeruginosa had a more long-standing disease and worse lung function. Radiological severity of the disease was mainly related to impaired lung function, P. aeruginosa isolation in sputum and frequent exacerbations. Conclusion: Data indicate that in Greece, "past" tuberculosis remains an important cause of bronchiectasis. P. aeruginosa was the predominant pathogen in the airways, associated with disease severity, while the most common lung function impairment was obstruction. Highlights: 277 non-CF bronchiectasis patients were examined prospectively. Post-infectious and past tuberculosis were the most common aetiologies. Past tuberculosis remains a significant cause of bronchiectasis in Greece. Bronchiectasis due to COPD is an increasingly recognized entity. Pseudomonas aeruginosa isolation was associated with several aggravating factors.